A novel approach to exploring glassy alloys with high oxidation resistance in the supercooled liquid region. (October 2016) - Lim, Ka Ram; Cho, Tae Hee; Park, Sung Hyun; Na, Min Young; Kim, Kang Cheol; Na, Young Sang; Kim, Won Tae; Kim, Do Hyang
Highlights: The characteristics of the oxide film is closely associated with Al content in Ni45 Zr35-x Ti20 Alx glassy alloys. The glass stability of the amorphous metal oxide can be strongly enhanced by codoping more than one stabilizer. Codoping Al and Ti into the amorphous zirconia film can be an effective way to protect the metallic glass substrate in the supercooled liquid region. Abstract: In the present study, we propose a novel approach to exploring glassy alloys with high oxidation resistance in their supercooled liquid region. The oxidation resistance of the Zr-based metallic glasses can be strongly enhanced when the glassy surface is covered by a native amorphous metal oxide film. We have investigated the effect of codoping Al and Ti into the amorphous zirconia on glass stability of the amorphous oxide by selecting Ni45 Zr35-x Ti20 Alx quaternary metallic glass system. The thermogravimetric analysis suggests that codoping multi-components is an effective way to enhance the glass stability of the amorphous oxide film.